A clinical study of diagnostic hysteroscopy in abnormal uterine bleeding and its histopathological correlation - Kumaresan, Shanmugapriya; Perumal, Devika (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Abnormal uterine bleeding is a common clinical problem with myriad of causes. The diagnosis and management of abnormal menstrual function must be based on an understanding of the physiologic mechanisms involved in the regulation of the normal cycles. Diagnostic hysteroscopy is a valuable tool in diagnosing structural intra-cavital pathology, very suitable for out-patient clinic. Methods: This is a prospective study which has been carried out in the Department of Obstetrics and Gynecology, Tirunelveli medical college hospital, Tirunelveli, Tamil Nadu from January 2011 to October 2011. Results: A total of 50 cases were analysed among the 50 patients tested. 26 patients had some pathology of which 24were accurately detected by hysteroscopy, missed 2 cases of irregular shedding endometrium which was reported by histopathology. Conclusions: Hysteroscopy is a safe, reliable and quick procedure in the diagnosis of cases with abnormal uterine bleeding with high sensitivity, specificity and negative predictive value.